2009
DOI: 10.1002/hep.22912
|View full text |Cite
|
Sign up to set email alerts
|

Targeting heat shock protein 90 with non-quinone inhibitors: A novel chemotherapeutic approach in human hepatocellular carcinoma

Abstract: The inhibition of heat shock protein 90 (Hsp90) has emerged as a promising antineoplastic strategy in diverse human malignancies. Hsp90 has been predicted to be involved in hepatocellular carcinoma (HCC) development; however, its role in hepatocarcinogenesis remains elusive. Using chemically distinctive Hsp90 inhibitors, we show that Hsp90 capacitates the aberrant expression and activity of crucial hepatocarcinogenesis-driving factors (e.g., insulin-like growth factor receptor 1, hepatocyte growth factor recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 39 publications
3
65
0
1
Order By: Relevance
“…Such compounds do not degrade NQO1 but still show HSP90 inhibition (39), and they might be more efficacious with reduced toxicity. It is possible that the benzoquinone moiety binding to mitochondria may explain the liver toxicity of 17AAG observed clinically (5,40,41). Others have shown that tumor cells organize an intramitochondrial HSP90 and TRAP-1 chaperone network and regulate mitochondrial permeability transition (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such compounds do not degrade NQO1 but still show HSP90 inhibition (39), and they might be more efficacious with reduced toxicity. It is possible that the benzoquinone moiety binding to mitochondria may explain the liver toxicity of 17AAG observed clinically (5,40,41). Others have shown that tumor cells organize an intramitochondrial HSP90 and TRAP-1 chaperone network and regulate mitochondrial permeability transition (8).…”
Section: Discussionmentioning
confidence: 99%
“…However, targeting mitochondria could also account for toxicity, e.g., through ROS generation. Because this activity is independent of inhibiting HSP90 chaperone function, diminishing the benzoquinone moiety's toxicity in future drugs should be considered (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of total protein lysates from cell cultures as well as subsequent SDS-PAGE and Western immunoblotting was performed as previously described (16). See Supplementary Material for the antibodies employed.…”
Section: Western Immunoblottingmentioning
confidence: 99%
“…Inhibition of a broadspectrum tumorigenic mechanism is resulted when HSP90 is targeted in vitro and in vivo. Independent of the etiological background, all HCC cell lines responded to HSP90 inhibition similarly with increased cell cycle arrest and apoptosis (Breinig et al, 2009). It might due to the fact that HSP90 inhibition triggered a simultaneous degradation of various hepatocarcinogenesis driving factors.…”
Section: Heat Shock Protein 90mentioning
confidence: 99%
“…In vivo studies showed that inhibitor of HSP90 is tumor-cell specific, and is able to efficiently reduce HCC tumor growth. Newly developed HSP90 inhibitor showed a lack of significant hepatotoxicity and is more tolerated, which become more practical in therapeutic treatment (Breinig et al, 2009). HSP90 inhibition further prevents tumor growth by disruption of tumor angiogenesis, as demonstrated by blocking PDGFR-expression in vascular smooth muscle cells and VEGF2 expression on endothelial cells (Lang et al, 2009).…”
Section: Heat Shock Protein 90mentioning
confidence: 99%